Pathophysiology and Clinical Applications of Nitric Oxide. - Rubanyi, Gabor M. (CRC Press, 1999)
Research on the key mediator nitric oxide has increased exponentially over the last ten years. It is now clear that, in addition to its role within the cardiovascular system, this mediator is also implicated in the normal physiological function and disease pathology of several organs and systems. A number of the fundamental research observations are now being developed into therapeutic principles and these are being pursued through clinical trials. This is the first work summarizing, in its two volumes, the quantum leap from basic science to clinical applications emerging from this decade of.